Analisis Kebutuhan Informasi Siswa Kelas XII di SMA Khadijah Surabaya - Mawaddah Anindya Estiningtyas (Universitas Wijaya Kusuma Surabaya, 2021)
This study is to describe the information needs of XII class students in Khadijah Surabaya Senior High School. The research method used is descriptive quantitative and the research location is in Khadijah Surabaya Senior High School. The population was taken from XII students class and a valid sample filled out the questionnaire as many as 68 students. The sampling technique was Purposive Sampling. The result of the research shows that 11 (eleven) indicators derived from David Nicholas used by the researcher produce 36 derivative indicators for the research questionnaire. From the 36 questions, 34 indicators show a high category score. While the remaining 2 show a score that is in the medium category. Indicators that are in the medium category have the lowest score. Those are the respondent’s information needs about technological and communication developments and the information needs of respondents who have an intellectual level of information that is filled with writing or words. On the other hand, the result of the highest score was found in the respondent’s information needs indicator showing that respondents need more information with a visually pleasing collection – book, magazine, or any other forms of information sources. Keyword: Analysis of Information Needs; Student Information Needs; Library School